Biology of western flower thrips (Frankliniella occidentalis) on English cucumbers and roses - Gaum, Wilma Gwendolene (Stellenbosch : Stellenbosch University, 2012)
Thesis (MScAgric) -- University of Stellenbosch, 1993.